Exercising the right to tax inspection between the privileges of the tax administration and the rights of the taxpayer in Algerian law - Chahinaz, Boudouh Majda (The International tax journal, 2025)
The tax administration establishes the tax based on determining the tax base for the taxpayer, and the law has enabled it to carry out a set of investigative procedures to collect evidential proof to confront the taxpayer in case they contest the administration's assessment. Among these procedures is the right to access, which allows tax administration officials to verify the accuracy of the information declared by the taxpayer and its consistency with their financial obligations. The tax right of access is considered one of the privileges of public authority used by the administration; however, it is obligated to uphold the rights of the taxpayer, or it will be subject to judicial oversight. Has the legislator organized this right in a way that preserves the rights of both parties: the tax administration and the taxpayer?